1995
DOI: 10.1007/bf01267721
|View full text |Cite
|
Sign up to set email alerts
|

Divorce-risk trends in Sweden 1971–1993

Abstract: "The purpose of this paper is to introduce an updated system of annual indexes of divorce risks and to use the system to display trends in divorce risks for Swedish women over the years since 1971. Divorce-risk trends turn out to have been quite different for women at different parities. Trends for women in their first marriage (the majority) are also somewhat different from trends in later marriages. After a spurt in divorces at parity 0 connected with a divorce reform in 1974, divorce risks have been quite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 8 publications
2
34
0
2
Order By: Relevance
“…(Of course, if estimating the effect of the folk belief on cohort fertility, cohort outcomes would be the dependent variable.) In the case of the speed premium in Sweden, tempo is a large part of the period effect, and its precise detail allows a strong case to be made for a causal influence of legislation relating to maternity-pay provision on fertility (Andersson 1999;Hoem 1990;Ní Bhrolcháin and Dyson 2007). The same applies to less-pronounced period fluctuations.…”
Section: Are Timing Effects a Source Of Bias In Period Fertility As Dmentioning
confidence: 91%
See 2 more Smart Citations
“…(Of course, if estimating the effect of the folk belief on cohort fertility, cohort outcomes would be the dependent variable.) In the case of the speed premium in Sweden, tempo is a large part of the period effect, and its precise detail allows a strong case to be made for a causal influence of legislation relating to maternity-pay provision on fertility (Andersson 1999;Hoem 1990;Ní Bhrolcháin and Dyson 2007). The same applies to less-pronounced period fluctuations.…”
Section: Are Timing Effects a Source Of Bias In Period Fertility As Dmentioning
confidence: 91%
“…The record of investigations conducted along these lines is decidedly positive. Demonstration of the speed-premium effect in Sweden by a set of regression standardized indicators had no need of stable assumptions (Andersson 1999;Hoem 1993). None of the three most informative decompositions of tempo and quantum-those of Butz and Ward (1979), Foster (1990), and Ryder (1980)-required stable population assumptions, nor did Lee's (1980) moving target theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was one of the conclusions of the review of the literature on causes of divorce [White, 1990]. In the United States [White and Booth 1985, Wineberg 1988, Waite and Lillard 1991 and in Sweden [Andersson 1995] it was found that the presence of young children was associated with lower risks of divorce. The presence of children younger than six years decreased the risk of marital dissolution in Australia, but once the employment activity of the wife was simultaneously taken into account, the effect of having young children disappeared [Bracher et al 1993].…”
Section: Overview Of Factors Which May Influence Divorcementioning
confidence: 99%
“…In terms of marital dissolution, Sweden is a country where divorce is easy to achieve; legislation that included no-fault grounds for divorce was introduced in 1915 (Sandström 2011). In 1974 the divorce legislation was liberalized further, which resulted in a pronounced increase in divorce risk levels (Andersson 1995(Andersson , 1997. The trend of increasing divorce risk became visible earlier in Sweden than in other countries in Europe.…”
Section: Marriage Formation and Divorce In Swedenmentioning
confidence: 99%